(untitled) (Research, Society and Development, 2021)
The industrial complex of Barcarena-PA was created, by means of a bilateral agreement between Brazil and Japan, in 1976, with that the municipality presents a great industrial growth over the years and consequently a large amount of deforested area. The objective of this work was to analyze the multitemporal images of the vegetal cover of the Industrial Complex in the municipality of Barcarena-PA, between the years 2006 to 2016. The methodology consists in the use of geotechnologies in order to classify the slicing of the multitemporal images with the use of NDVI due to the susceptible occupational changes that occurred in the region of the Industrial Complex. The results showed significant changes over the years, due to the installation of companies, and the great population growth that, due to not having housing in the cities, started to invade forested areas around the city.